Grenada : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
This 2005 Article IV Consultation highlights that real GDP growth in Grenada, on average, has been low over the last five years compared with growth of nearly 6 percent a year in the late-1990s. Inflation has remained low and stable within the framework of the currency board arrangement. The annual inflation rate in April 2005 was 1.8 percent. External current account deficits have been large, although mostly financed by foreign direct investment and capital transfers. Financial sector indicators have also strengthened in recent years.